TEORI PROGRESIVISME JOHN DEWEY DAN PENDIDIKAN PARTISIPATIF DALAM PENDIDIKAN ISLAM - Tria Wulandari (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2020)
This article contains the concept of participatory education that is applied in the world of education so far not been implemented to the fullest. There are still a few things that need to be improved especially in Islamic education. After knowing the problem, the writer tries to solve the problem using John Dewey's theory of progressivism. John Dewey's theory of progressivism when associated with participatory education that both have the same goal. Both when combined will make it easier for students to find experience through self-exploration and find their potential in solving problems that will be faced in the future and have a change (progress) better. In implementing participatory education with John Dewey's theory of progressivism in Islamic education it needs to be filtered back with the values that have been prescribed in Islam. If it is positive, not contradictory and beneficial, it needs to be applied. However, if there are things that are contrary to Islamic values then it does not need to be applied, it is enough to be used as knowledge.